2020
DOI: 10.1111/jfbc.13413
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan‐stabilized selenium nanoparticles attenuate acrylamide‐induced brain injury in rats

Abstract: Acrylamide (CH 2 = CHCONH 2) is an organic compound that is soluble in water and formed in food when exposed to high temperatures. Studies have shown that acrylamide is one of the causes of cancer, as well as affecting the brain and the natural balance of hormones in humans (Batoryna, Lis, & Formicki, 2017). Various studies have reported several harmful effects in experimental rats due to acrylamide administration, such as neuropathy, low tendon reflexes, muscle weakness, behavioral disorders, and toxic sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 38 publications
(63 reference statements)
1
7
0
Order By: Relevance
“…In this aspect, De Giglio et al recommended the necessity of using chitosan nanoparticles in biological experiments to influence the efficacy at the level of dopamine production . What is more, a previous study indicated that chitosan-stabilized selenium nanoparticles attenuate acrylamide-induced abnormal DA and NE in the blood serum and the cerebral cortex region of male rats, which is consistent with our experimental results …”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In this aspect, De Giglio et al recommended the necessity of using chitosan nanoparticles in biological experiments to influence the efficacy at the level of dopamine production . What is more, a previous study indicated that chitosan-stabilized selenium nanoparticles attenuate acrylamide-induced abnormal DA and NE in the blood serum and the cerebral cortex region of male rats, which is consistent with our experimental results …”
Section: Resultssupporting
confidence: 91%
“…44 What is more, a previous study indicated that chitosan-stabilized selenium nanoparticles attenuate acrylamide-induced abnormal DA and NE in the blood serum and the cerebral cortex region of male rats, which is consistent with our experimental results. 45 The prefrontal cortex is the only cortical region that sends projection signals directly to the hypothalamus. It exerts corticalmediated inhibitory effects on the CRF/HPA axis and the sympathetic nervous system.…”
Section: Protective Effects Of Senps On the Basal Metabolic Index In ...mentioning
confidence: 99%
“… 66 , 75 , 76 Chitosan-stabilized Se nanoparticles also displayed more antioxidant power toward acrylamide-induced neural damage, as demonstrated by reduced cerebral MDA and NO levels and increased GSH levels. 77 The antioxidant potential of PDGs may also be associated with free radical-scavenging properties and the ability to interfere with NOS activity to suppress NO production. 20 PDGs have also been demonstrated to effectively inhibit ROS production associated with hypoxia-mediated brain injury by minimizing nitrotyrosine formation and hindering blood–brain barrier leakage, which suppresses CD11b leukocyte infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…They were purified in xylene and fixed in paraffin at 56° in a hot air oven for 24 h. Tissue paraffin blocks of 4 µm thickness were obtained using slidge microtome. The tissue blocks were placed on glass slides, deparaffinized, stained by hematoxylin and eosin stains, and scanned by the electric light microscope for histopathological inspection [25]. Hence, the extent of drug solubility in lipid excipients greatly affects the drug loading; it was expected to choose oleic acid for NLCs preparation.…”
Section: Histopathological Analysismentioning
confidence: 99%